A new species of Homonota (Squamata, Gekkonidae) from Paraguay, with a key to the genus - Cacciali, Pier; Ávila, Ignacio; Bauer, Frederick (Phyllomedusa: Journal of Herpetology, 2007)
A new species of Homonota (Squamata, Gekkonidae) from Paraguay, with a key to the genus. A new species of Homonota from Paraguay is described. The new taxon can be differentiated from other species in the genus by the body and head pholidosis as well as the coloration. Homonota sp. nov. seems to be very similar to H. uruguayensis, with which it shares the ecological preference of rocky environments, but both are different in their pholidosis. Homonota sp. nov. is currently only known from the type locality and is the only gekkonid lizard that inhabits the Alto Paraná Atlantic Forest of Paraguay. An identification key for the species of the genus Homonota is provided.